Efektivitas Media Sosial dalam Komunikasi Korporat: Studi Observasi pada BCA, Mandiri, BNI, dan BRI - Dewi, Agatha Anggraeni; Arifin, Fian Khamil; Sudarmanti, Rini (Da’watuna: Journal of Communication and Islamic Broadcasting, 2026)
Social media has become a key tool in corporate communication, yet not all digital activity leads to meaningful engagement. This study observed the social media performance of BCA, Mandiri, BNI, and BRI from May 12 to 25, 2025, using a descriptive quantitative method. The analysis included posting frequency, platform use, follower count, and engagement rate per post (ERP). Findings reveal that Mandiri, despite having the fewest followers, achieved the highest engagement, while BNI and BCA—both with large audiences—showed lower effectiveness. These results highlight the importance of content quality and platform strategy in building effective digital relationships.